Neuroprotective Effects of Deproteinized Calf Serum in Ischemic Stroke - Li, Weiwei; Guo, Anchen; Sun, Ming; Wang, Jiachuan; Wang, Qun (Frontiers in Neurology, 2021)
Deproteinized calf serum (DCS) may have neuroprotective effects after ischemic stroke. The aim of this study is to investigate whether and how the DCS inhibits neuronal injury following cerebral ischemia. Rats were subjected to 2 h transient middle cerebral artery occlusion (MCAO). One dose of 0.125 mg/gbw DCS was given immediately after reperfusion. Neurological deficit and infarct volume at 24 h post-MCAO in DCS-treated rats were lower than those in vehicle-treated rats (p < 0.0005). In cultured neurons model, cell viability was decreased, and apoptosis was increased by oxygen-glucose deprivation/reperfusion (OGD/R) (p < 0.0005). These effects of OGD/R were attenuated by 0.4 μg/μl DCS (p < 0.05) that were validated by CCK8 cell viability assay, phycoerythrin–Annexin V Apoptosis Detection assay, and TUNEL assay. Furthermore, the increase of intracellular ROS level in cultured neurons was suppressed by DCS (p < 0.05). Compared with cells subjected to OGD/R, the expression level of Bax protein decreased, and bcl-2 protein increased after DSC treatment (p < 0.05). Overall, the neuroprotective effects of DCS following cerebral ischemia may in part be due to decreased ROS production and inhibition of apoptosis.